GOALS AND OBJECTIVES OF IMPROVING METHODS FOR DEVELOPING THE COGNITIVE SKILLS OF PRIMARY STUDENTS THROUGH HAND-MOTOR EXERCISES (International journal of artificial intelligence, 2026)
This article analyzes the theoretical part of the methods for developing the cognitive abilities of primary school students, and discusses the goals and objectives of the methods developed for primary school students in accordance with their age, along with the improvement of these methods.